2007
DOI: 10.1007/s00464-006-9135-2
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-alignment surgical skills assessment

Abstract: Reverse-alignment surgical skills can be improved with experience, but may require a volume of cases exceeding that encountered in residency training. Reverse image skills are not derivative from surgical skills developed in a video trainer with forward orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…Gould and Frydman [10] reported similar results when they assessed surgical residents and attending surgeons performing various laparoscopic tasks. They demonstrated a 65 and 470% decline in task performance in attending surgeons and residents, respectively, when performing the tasks within the paradoxical viewpoint [10].…”
Section: Discussionsupporting
confidence: 53%
“…Gould and Frydman [10] reported similar results when they assessed surgical residents and attending surgeons performing various laparoscopic tasks. They demonstrated a 65 and 470% decline in task performance in attending surgeons and residents, respectively, when performing the tasks within the paradoxical viewpoint [10].…”
Section: Discussionsupporting
confidence: 53%
“…In a recent study, a significantly longer period was required to perform a procedure in reverse alignment compared with forward alignment, and surgeons with experience in laparoscopic procedures completed the task more rapidly than did novices in reverse-alignment conditions [6]. In another study, a marked deterioration in the execution of laparoscopic procedures was observed for reverse-alignment situations compared with normal viewing [7].…”
Section: Discussionmentioning
confidence: 95%
“…Under such conditions, the mirror image of the operative field can disorient the assistant, potentially degrading the performance of their task. Several studies have measured surgical performance under mirror-image conditions in the experimental setting [6][7][8]; however, there are few reports on the extent of difficulties and progressive improvement in performance under reverse alignment conditions in the clinical setting. The present study attempted to examine the learning curve of the assistant during laparoscopic colorectal surgery from the viewpoint of overcoming problems associated with the mirror-imaging effect.…”
mentioning
confidence: 98%
“…The extant literature has demonstrated (i) performance advantage when the head and hands are pointed in the same direction during visual-motor tasks; (ii) a subjective preference of surgeons for the visual angle to be at 0 ; and (iii) an improved ability in experienced surgeons to deal with rotations of the visual display compared with less experienced surgeons. 11,12 These studies have not quantified the effects of head rotation/viewing angle on visual-motor control processed in MIS and thus the extent to which visual transformations modulate motoric control processes is unclear. Therefore, an empirical investigation into the role of monitor angle on motoric performance in MIS is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies in the surgical literature have suggested that incomplete decoupling of head position signals during surgical tasks results in significant performance costs in MIS. [9][10][11][12][13] Generally, studies imply that MIS monitors should be positioned in front of the surgeon, and at eye level, in order to minimize inconsistency between the hand and eye. 9,13 Positioning the monitor head-on to the surgeon performing the procedure is also more likely to yield optimal performance 12 and, as a small-scale study suggests, is also a surgeon's preferred setup.…”
Section: Introductionmentioning
confidence: 99%